 a^{m} x a^{n} = a^{m+n}
 a^{m}/a^{n} = a^{mn}
 (a^{m})^{n} = a^{mn}
 a^{–m} = a^{1/am}
 m√a = a^{1/m}
 (ab)^{m} = a^{m} . b^{m}
 a^{0} = 1
 a^{1} = a
 √a+√a+√a + ∞ = a
 √a+√a+√a + ∞ = (1 ± √1 + 4a )/2

If a/b = c/d = e/f , then each of these ratios is equal to (a+c+e)/(b+d+f)

If a : b = c : d, then ad = bc = b : a = d : c a : c = b : d
If a : b = c : d, then If a:b = c:d, then ad = bc, b:a = d:c, a:c = b:d
If three quantities a, b and c are such that a : b :: b : c, then we say that they are in CONTINUED PROPORTION. We also get, b^{2} = ac.

Direct variation: If A ∝ B, then A_{1}/A_{2} = B_{1}/B_{2}
Inverse variation: If A ∝ 1/B, then A_{1}B_{1} = A_{2}B_{2}
Ratio
Proportion
Variation
x as a percent of y = X/Y x 100
y as a percent of x = Y/x x 100
Percentage Increase = (Final initialinitial) x 100 =(Difference/smaller) x 100.
Percentage More (or) Percentage Exceeding = (Difference/smaller) x 100.
Percentage Less (or) Percentage Decrease =(Difference/Greater) x 100.
If the price of a commodity increases by r%, then the reduction in consumption so that the expenditure remains the same, is ( (r /100 + r) x 100)%
If the value of a variable is first increased x% and then decreased by y%, then there is ( (X Y) XY/100)% increase or decrease, according to the +ve, or –ve sign respectively.
If the value of a number is first increased by x% and later decreased by x%, the net change is always a decrease which is equal to X^{2}/100%
Instead if it decreases, increase in consumption = ( (r /100  r) x 100)%
Profit = Selling Price (S.P) – Cost Price (C.P)
When S.P. > C.P.,
 Profit = S.P. – C.P.
 S.P. = C.P. + Profit
 C.P. = S.P. – Profit
Profit % = (Profit/C.P.) X 100
S.P. = C.P. X (100 + Profit%)/100)
When S.P. < C.P., Loss = Cost Price (C.P) – Selling Price (S.P)
Loss % = ( Loss /C.P) X 100
S.P. = C.P. X ( 100  Loss%)/ X 100
When there are two articles having the same cost price and if one article is sold at a% profit and the other is sold at a% loss, profit % or loss % is zero.
If there are two articles having the same selling price and one is sold at x% profit and the other is sold at x% loss, effectively, a loss will always be made and the loss percent is(X/10)^{2} %
Discount = M.P. – S. P.
Discount % = ( Discount/M.P.) x 100
When M.P and Discount % are given,
S.P. = (M.P. X (100  Diccount&))/100When an article is sold after two successive discounts of p% and q%, then the final selling price = M.P.((100p)(100q))/100 x 100.
If cost price of x articles is equal to the selling price of y articles, then profit or loss percentage =(X  Y/Y) x 100 %
If the shopkeeper sells goods at cost price but gives lesser weight than true weight, then
Gain percentage =(True weight  False weight)/(False weight) x 100If the shopkeeper sells his goods at a% loss on cost price but uses b gm instead of c gm, then his % profit or loss [100  a] c/b  100 is as the signis +ve or –ve.
Simple Interest = PTR/100.
Amount (A) = P(1 + TR/100)
Compound interest = P[(1 + R/100)  1]
Amount under C.I = P(1 + R/100)
If a sum becomes x times in y years at CI then it will be (x)^{n} times in ny years.
If a sum of money becomes ‘m’ times in ‘t’ years at SI, the rate of interest is given by
(a) (100 (m  1))/t %
(b) Also to become n times, time taken = (n  1) x t/(m  1)If amount under Compound Interest for n years and (n + 1) years is known, then the rate of interest is given by
(Difference of amount after n yrs and (n+1)/rs x 100)/Amount after n yrsDifference between the compound interest and simple interest on a certain sum of money for 2years at r% rate is given by
Sum(r/100)^{2}Difference between CI and SI on a certain sum for 3 years at r% is given by
P(r/100)^{2} (r/100 + 3)
Average = Sum of all items in the group/Number of items in the group.
Quantity of Cheaper/Quantity of Dearer = Rate of deared  Average Rate/Average Rate  Rate of Cheaper
Work and men are directly proportional to each other, i.e.,
 Men and days are inversely proportional
 Men and hours are inversely proportional
Joint variation of the above can be written as
M_{1}D_{1}H_{1}/W_{1} = M_{2}D_{2}H_{2}/W_{2}If A can do a piece of work in x days and B can do it in y days, then A and B working together will do the same work in XY/(X + Y) days
If a pipe can fill a tank in x hours , and another pipe can empty the full tank in y hours, then the time taken to fill the tank, when both the pipes are opened = XY/(X  Y)
Speed
Distance covered per unit time is called speed.
i.e., Speed = Distance/Time
If two bodies travel with the same speed, Distance covered µ Time (Direct Variation).
If two bodies travel for the same period of time, Distance covered µ Speed (Direct Variation).
If two bodies travel in the same distance, Time ∝ 1/Speed (Inverse Variation)
Joint variation of these is Speed ∝ Distance/Time
To convert speed in kmph to m/sec, multiply it with (5/18).
To convert speed in m/sec to kmph, multiply it with (18/5).
Relative Speed:
(i) In the same direction, difference of the speeds of the two bodies.
(ii) In opposite direction = Sum of the speeds of the two bodies.
Average Speed = Total distance travelled/Total time taken
(a) If a person travels a distance at a speed of x km/hr and the same distance either in the same direction or the other way at a speed of y
km/hr, then the average speed during the whole journey is given by 2XY/X + Y km/hr(b) Instead if distances are in the ratio m : n, then average speed = ((m + n)xy)/my + nx
Speed of the boat against stream (or) Upstream Speed = Speed of the boat in still water – Speed of the stream.
Speed of the boat with the stream (or) Downstream Speed = Speed of the boat in still water + Speed of the stream.
If two persons cover a certain distance at different speeds reaching at different times, then that distance = (Product of two speeds)/(Difference of two speeds) x Difference between arrival times
If two persons A and B start at the same time in opposite directions form two points and after passing each other they complete the journey in 'a' and 'b' hrs respectively, then A's speed : B's
speed = √b : √a
Trains
Time taken by a train of length ℓt travelling at a speed of s_{t} to cross a
(a) pole (or) a tree = ℓ_{t}/s_{t}
(b) platform of length ℓ_{p} = (ℓ_{t} + ℓ_{p})/s_{t}
Time taken by two trains of lengths ℓ_{1}and ℓ_{2} travelling at speeds of s1 and s2 to cross each other is given by
= (ℓ_{1} + ℓ_{2})/(s_{1} + s_{2}) (opposite Direction) = (ℓ_{1} + ℓ_{2})/(s_{1} ∼ s_{2})(Same Direction)
Circular Tracks
When two people are running around a circular track starting at the same time from the same point, we would be interested in finding out the time taken by them to meet for the first time anywhere on the track or to meet for the first time at the starting point.
They start running from the same point at the same time. Then the following table gives complete details for finding out the time required for various meetings as discussed above.
SituationTime taken  Two people A and B running in opposite directions  Two people A and B running in the same direction  Three people A, B and C running in the same direction 

To meet for the first time anywhere on the track  Length of the track/Relative Speed = L/(a + b)  Length of the track/Relative Speed = L/(a  b)  LCM of{L/(a – b),L/(b – c)} 
To meet for the first time at the starting point  LCM of {L/a, L/b}  LCM of {L/a, L/b}  LCM of {L/a,L/b, L/c} 
In a regular polygon of n sides, each of the interior angles.
d =( (2n  4) /n )x 90°
Each exterior angle = 360^{o}/n
No. of diagonals = n(n  3)/2
Area of a regular polygon = 1/2 x Perimeter x Perpendicular distance from the centre to any side.
MENSURATION
Triangles
For any triangle
(a) When the measurements of sides a, b, c are given, Area = √s(s  a)(s  b)(s  c)
where s = ^{(a + b + c)}/_{2}(b) When height and base are given, Area = 1/2 x Base x Altitude = 1/2 a.h
(c) Area = 1/2 ab . sinC = 1/2 bc.sinA =1/2 ca.sinB
(d) Area =^{(abc)}/_{4R} where R is the circumradius.
(e) Area = s.r where r is the inradius.
(a) For a right angled triangle, area = 1/2 x Product of the sides containing the right angle.
(b) In a right angled triangle, circumradius = ^{hypothenuse/2 }
For an equilateral triangle, area =^{√3 . a 2}/_{4} where "a" is the side of the triangle. =^{√3 . a}/_{4}

For an isosceles triangle where "a" is length of two sides which are equal and b is the third side.
Area = b/4 √4a^{2}  b^{2}
Quadrilaterals

For any quadrilateral
(a) Area = 1/2 x one diagonal x sum of offsets (or perpendiculars) drawn to this diagonal from the two opposite vertices
(b)Area = 1/2 x Product of diagonals x Sine of the angle between them
= 1/2 . AD.BC.sinq 
For a cyclic quadrilateral, Area
=√(s  a)(s  b)(s  c)(s  d) where s is the semiperimeter, i.e., s = (a + b + c + d)/2 
For a trapezium, area = 1/2 x Sum of parallel sides x Height

For a Parallelogram
(a) Area = Base x height
(b) Area = Product of two sides x Sine of included angle 
Rhombus, Area = 1/2 x Product of the diagonals Side = 1/2 √sum of the squares of diagonals

For a Rectangle, Area = Length x Breadth

For a Square
(a) Area = side^{2}
(b) Area = 1/2 x Diagonal^{2} [Diagonal =√2 x Side] 
For a Polygon
(a) Area of a regular Polygon = 1/2 x height x perimeter of the polygon (where height is the perpendicular distance from the centre to any side. Please note that the centre of a regular polygon is equidistant from all its sides)
(b) For a polygon which is not regular, the area has to be found out by dividing the polygon into suitable number of quadrilaterals and triangles and adding up the areas of all such figures present in the polygon.
In measuring the sides of a rectangle, one side is taken x% in excess and the other y% in deficit. The error percent in area calculated from the
measurement is X  Y  XY/100 in excess or deficit, according to the +ve or –ve sign.
If the side of a triangle, rectangle, square, circle, rhombus (or any 2  dimensional figure) are increased by x% its area is increased by (x(x + 200))/100 % or [2x + x^{2}/100]%
Circle

Area = πr^{2} where r is the radius of the circle. Circumference = 2πr

Sector of a circle: Area =Θ/360 x πr^{2} Where θ is the angle of the sector and r is the radius of the circle. Length of arc = Θ/360 x2πr

Circular ring : Area = πR^{2} – πr^{2} = π(R + r)(R  r)
Solids
Solids are threedimensional objects which, in addition to area, have volume also. For solids, two different types of areas are defined
(a) Lateral surface area or curved surface area and
(b) Total surface area.
For any solid, whose faces are regular polygons, No. of faces + No. of vertices = No. of edges + 2
Prism
Lateral surface area = perimeter of base x height
Total surface area = Lateral Surface Area + 2 x Area of base
Volume = area of Base x height
Cuboid
Lateral surface area = 2(ℓ + b).h, where
Total surface area = 2(ℓ + b)h + 2 ℓb = 2(ℓb + ℓh + bh)
Volume = ℓbh
Longest diagonal of the cuboid = √ℓ^{2} + b^{2} + h^{2}Cube
Volume = a^{3} where "a" is the side of the cube.
Lateral surface Area = 4a^{2} and Total Surface Area = 6a^{2}
Cylinder
Volume = Πr^{2}h, where "r" is the radius of the base and "h" is the height
Curved surface area = 2Πrh and Total Surface Area = 2 Πrh + 2Πr^{2} (or) 2Πr(r + h)
A hollow cylinder has a crosssection of a circularring.
Volume of the material contained in a hollow cylindrical ring = Π(R^{2} – r^{2})h where R is the outer radius, r the inner radius and h1 the height.
Cone
A cone is equivalent to a right pyramid whose base is a circle. Volume = 1/3 Πr^{2}h ; Where r is the radius of the base, h is height of the cone and ℓ is the slant height. Curved surface area = Π r. ℓ;
Total surface area = Π r ℓ + Π r^{2} = Π r(ℓ + r)
Sphere
Surface area of a sphere = 4Πr^{2}, where r is radius.
Volume of a sphere = (4/3)Πr^{3}

Union of Sets:
 A ∪ B = {x │x∈A or x∈B}
 If A ⊂ B, then A ∪ B = B
 A ∪ φ = A
 A ∪ μ = μ

Intersection of Sets:
 A ∩ B = {x  x ∈ A and x ∈ B}.
 A ⊂ B, then A ∩ B = A.
 A ∩ φ = φ.
 A ∩ μ = A.

Difference of Sets:
 A  B = {x  x ∈ A and x ∈ B}
Similarly, B  A = {x ∈ B│ x ∉ A}
 A  B = {x  x ∈ A and x ∈ B}
 A Δ B = (A ∪ B) – (A ∩ B) = (A – B) ∪ (B – A)

Some Results:
 A ∪ A = A; A ∩ A = A
 A ∪ B = B ∪ A
 A ∩ B = B ∩ A
 A ∪ (B ∪ C) = (A ∪ B) ∪ C
 A ∩ (B ∩ C) = (A ∩ B) ∩ C
 A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ C)
 A ∩ (B ∪ C) = (A ∩ B) ∪ (A ∩ C)
 C  (C  A) = C ∩ A
 C  (A ∩ B) = (C  A) ∪ (C  B)
 C  (A ∪ B) = (C  A) ∩ (C  B)
 (A^{c})^{c} = A
 (A ∪ B)^{c} = A^{c} ∩ B^{c}
 (A ∩ B)^{c} = A^{c} ∪ B^{c}
 A Δ B = (A – B) ∪ (B – A) = (A ∪ B) – (A ∩ B)
 n(A ∪ B) = n(A) + n(B) –n(A ∩ B)

Cartesian Product of Two Sets:
Let A and B be any two sets. Then the cartesian product of A and B is the set of all ordered pairs of the form (a, b), where a ∈ A and b ∈ B.
The product is denoted by A ´ B
A x B = { (a, b)│ a ∈ A, b ∈ B}
 A x B ≠ B x A
 n(A x B) = n(B x A) = n(A) x n(B)
 The number of relations defined from A to B = 2^{n(A) x n(B)}

Reflexive Relation:
 A relation R on a set A is said to be reflexive, if for every x ∈ A, (x, x) ∈ R.
 If 'A' has n elements then a reflexive relation must have at least 'n' ordered pairs.
 The number of reflexive relations defined from A to A = 2^{r2  1}.

Symmetric Relation:
A relation R on a set is said to be symmetric if (x, y) ∈ R ⇒ (y, x) ∈ R The necessary and sufficient condition for a relation R to be symmetric is R = R^{1}.

Transitive Relation:
A relation R on a set is said to be symmetric if (x, y) ∈ R ⇒ (x, z) ∈ R 
Equivalence Relation:
 A relation which is reflexive, symmetric and transitive is called an equivalence relation.
 The smallest equivalence relation on a set A is the identity relation.
 The largest equivalence relation on a set A is the cartesian product A x A.

Antisymmetric Relation:
R is antisymmetric if (a, b) ∈ R, (b, a) ∈ R ⇒ a = b

Partially Ordered Relation:
Let R be a relation on a set A, then R is said to be a partial order relation if it is reflexive, antisymmetric and transitive.
 Number of functions from a set A containing m elements to another set B containing n elements is n^{m}.
 f: A → B is oneone if x1 ≠ x2 ⇒ f(x1) ≠ f(x2), Equivalently f(x1) = f(x2) ⇒ x1 = x2.
 The number of oneone functions defined from set A to set B is ^{n(B)}p_{1}(A).
Onto Function (Surjection):
 If f is onto, range of f = codomain of f.
 If n(A) = m; n(B) = 2, then the number of onto functions defined from A to B is 2^{m} – 2.
OnetoOne Function (Injection):
Bijection:
If a function is both onetoone and onto, then it is called a bijective function or bijection. The number of bijective functions defined from A to B is m! where n(A) = n(B) = mComposite Function or Product Function:
If f: A → B and g : B → C are two functions, then g o f is a function from A to C, such that g o f(a) = g[f(a)], for every a Î A and is called the composite mapping of f and g. If f: A → B and g: B → C are two bijective functions, then (g o f)^{ 1} = f^{ 1} o g^{ 1}.
 If h: A → B, g: B → C and f: C → D be any three functions, then f o (g o h) = (f o g) o h.
 (f o f ^{ 1}) (x) = x or f o f^{ 1} = I.
Real Function:
Given below are the domain and range of the various trigonometric functions.
Function  Domain  Range 

sin x  R  [1, 1] 
cos x  R  [1, 1] 
tan x  R{(2n+1) φ/2  n ∈ Z }  R 
cot x  R  {nφ  n ∈ Z}  R 
sec x  R{(2n+1) φ/2  n ∈ Z}  ( ∞, 1] ∪ [1, ∞) 
cosec x  R{nφ  n ∈ Z}  ( ∞, 1] ∪ [1, ∞) 
 If p = T and q = T then p ∧ q = T
 If p = F, q = F then p ∨ q = F
 If p = T, q = F then p ⇒ q = F
 (p ⇒ q) = ∼ p ∨ q
 Converse of p ⇒ q = q ⇒ p
 Inverse of p ⇒ q = ∼p ⇒ ∼q
 Contropositive of p ⇒ q = ∼q ⇒ ∼p
 p ⇔ q = (p ⇒ q) ∧(q ⇒ p)
 ∼(p ∨ q) = ∼p ∧ ∼q
 ∼(p ∧ q) = ∼p ∨ ∼q
 ∼(p ⇒ q) =p ∧ ∼q
 ∼(p ⇔ q) = ∼p ⇔ q
= p ⇔ ∼q
Some Logical Equivalences:
 Commutative Properties:
p ∨ q ≡ q ∨ p ; p ∧ q ≡ q ∧ p  Associative Properties:
p ∨ (q ∨ r) ≡ (p ∨ q) ∨ r ; p ∧ (q ∧ r) ≡ (p ∧ q) ∧ r  Distributive Properties:
p ∨ (q ∧ r) ≡ (p ∨ q) ∧ (p ∨ r) ;
p ∧ (q ∨ r) ≡ (p ∧ q) ∨ (p ∧ r)  Idempotent Properties:
p ∨ p = p ; p ∧ p = p  Absorption :
p ∨ (p ∧ q) = p
p ∧ (p ∨ q) = q
List of Tautologies:
 p ∧ q ⇒ p or p ∧ q ⇒ q
 p ⇒ p ∨ q or q ⇒ p ∨ q
 ∼p ⇒ (p ⇒ q) or ∼(p ⇒ q) ⇒ p
 (p ∧(p ⇒ q)) ⇒ q
 (∼p ∧ (p ∨ q)) ⇒ q
 (∼q ∧ (p ⇒ q)) ⇒ ∼p
 ((p ⇒ q) ∧ (q ⇒ r)) ⇒ (p ⇒ r)
hypothetical syllogism or transitive rule
Operations with F and T:
(T – Tautology and F – Contradiction)
 p ∨ ∼p = T
 p ∧ ∼p = F
 T ∨ p = T
 F ∧ p = F
 F ∨ p = p
 T ∧ p = p
 ∼F =
 ∼T = F
 If a > b, then b < a
 If a > b and b > c, then a > c
 If a < b and b < c, then a < c
 If a > b and c > 0 then a ± c > b ± c
 If a > b and c > 0, then ac > bc
 If a < b and c > 0, then ac < bc
 If a > b and c < 0, then ac < bc
 If a < b and c < 0, then ac > bc
 If a > 0, then a < 0 and if a > b, then a < b
 If a and b are positive numbers and a > b, then 1/a < 1/b,
 If A, G and H are the Arithmetic mean, Geometric mean and Harmonic mean of n positive real numbers, then A ≥ G ≥ H, the equality occurring only when the numbers are all equal.
Properties of modulus:
 x = 0 ⇔ x = 0
 x ≥ 0 and – x ≤ 0
 x + y ≤ x + y
  x  y  ≤ x  y
 x ≤ x ≤ x
 xy = x . y
 x/y =y/x , y ≠ 0
 x^{2} = x^{2}
 A = , then A^{2} –(a + d) A = [bc – ad]I.
 If A = , then A^{n} =
 If A = , then det A = ad – bc
 If A is a n ´ n matrix, then det(KA) = K^{n} det A.
 det(A^{1}) =
 If A is a n ´ n matrix, then det(adjA) = (det A)^{n  1}.
 If A = , then adj A =
 If A = , then A^{–1} =
 det(AB) = detA.detB
 The nP_{r} and nC_{r} representation:
 For 0 ≤ r ≤ n,
nP_{r} = n!/(n  r)! and nC_{r} = n!/r!(n  r)!  nC_{r} = nC_{n}  r
 If nC_{r} = nC_{s}, then r = s or r + s = n
 For 0 ≤ r ≤ n,
 Binomial Theorem for a Positive Integral Index:
 If 'n' is a positive integer, then
(x + y)^{n} = nC_{0}x^{n} + nC_{1}x^{n  1}y^{1} + nC_{2}x^{n  2}y^{2}+..... + nC_{r}x^{n  r}y^{r} +…..+nC_{n}y^{n},  Number of terms in the expansion is n + 1
 General Term in the Expansion of (x + y)^{n} is
T_{r + 1} = nC_{r} x^{n  r} y^{r},  The general term in the expansion of (x  y)^{n is Tr + 1 = (1)r nCr xn  r . yr}
 If 'n' is even, there exists only one middle term, which is (n/2 + 1)^{n} term
 If 'n' is odd, there will be two middle terms i.e.(n + 1)/2 ^{n}and(n + 3)/2^{n} terms.
 The Greatest Coefficient in the Expansion of (1 + x)n (where n is a positive integer): is
= n/2 (if n is even)
n_{c} = (n + 1)/2 or n_{c} (n  1)/2 (if n is odd)  The coefficient of xk in the expansion(ax^{p} + b/x^{q})^{n} is T_{r + 1}, then r =( n_{p}  k )/p + q.
 The constant term in(ax^{p} + b/x^{q})^{n} is T_{r + 1}, then r =( n_{p} )/p + q. .
 The number of terms in (a + b + c)n is (n + 1)(n +2)/2
 If 'n' is a positive integer, then
 Numerically Greatest term in the Expansion of (1 + x)^{n}:
The numerically greatest term in the expansion of (1 + x)^{n} is found out using the following process. We calculate the value of ((n + 1)x)/x + 1: If ((n + 1)x)/x + 1 = an integer, say 'k', then k^{th} and (k + 1)^{th} terms are numerically greatest terms
 If ((n + 1)x)/x + 1 is not an integer, say k + a; where 0 < a < 1, (k + 1)^{th} term is numerically greatest term.

Properties of Binomial Coefficients:
 C_{0} + C_{1} + C_{2} + ....... + C_{n} = 2^{n}
i.e., sum of all the binomial coefficients in the expansion of (1 + x)^{n} is 2^{n}  C_{1} + C_{3} + C_{5} + . . . . =2^{n}/2 = 2^{n  1}
C_{0} + CC_{2} + C_{4} . . . . = 2^{n  1}
i.e. sum of coefficients of odd terms is equal to the sum of coefficients of even terms and each sum is 2^{n  1}  Let f(x) = (ax +b)^{n}
The sum of all coefficients = f(1)
The sum of even coefficients =(f(1) + f(1))/2
The sum of odd coefficients = (f(1)  f(1))/2  The ratio of the two successive terms in (ax + by)^{n} is T_{r}/T_{r + 1} = nr/n r + 1 (by/ax)
 C_{0} + C_{1} + C_{2} + ....... + C_{n} = 2^{n}

Expansions:
 (1  x)^{1 }= 1 + x + x^{2} + x^{3} + ........ + x^{r} + .......
 (1 + x)^{1} = 1  x + x^{2}  x^{3} + ....... + (1)^{r} x^{r} +......
 (1  x)^{2} = 1 + 2x + 3x^{2} + 4x^{3} + ........ + (r + 1)x^{r} + .......
 (1 + x)^{2} = 1  2x + 3x^{2}  4x^{3} + ....... + (1)^{r}(r + 1)x^{r} + ......

Remainder Theorem:
 If a polynomial, say f(x), is divided by (x  a), then the remainder is f(a).
 If f(x) is a polynomial such that f(a) = 0, then (x  a) is a factor of f(x).
 If the sum of the coefficients of all the terms in the polynomial f(x) is zero, then (x  1) is a factor of f(x).
 If the sum of the coefficients of odd powers of x is equal to the sum of the coefficients of even powers of x, then (x+1) is a factor.
 If f(x) is divided by ax + b, then remainder is f ( b/a).
 When a polynomial, say f(x) is divided by a polynomial p(x) to give a quotient q(x) and a remainder r(x), by division algorithm
Dividend = [Divisor x Quotient] + Remainder we have, f(x) = p(x) x q(x) + r(x)

Arithmetic mean (A.M. or ):
 Individual series: =
 Discrete series: = where x_{1}, x_{2}, .… x _{n} are n distinct values with frequencies f_{1}, f_{2}, f_{3}, …., f _{n} respectively.
 Continuous series: = = where f_{1}, f_{2}, f_{3} ,…. fn are the frequencies of the classes whose midvalues are m_{1}, m_{2}, … m_{n} respectively.
 The algebraic sum of deviations taken about mean is zero.
 Mean of first n natural numbers is (n+1)/2
 Arithmetic mean of two numbers a and b is (a + b)/2
 Combined Mean: If x1 and x2 are the arithmetic means of two series with n1 and n2 observations respectively, the combined mean,
 Geometric Mean (G.M.) for Individual series
 G.M. = (x_{1}. x_{2}. x_{3} …. x_{n})^{1/ n} ,
 Geometric mean of two numbers a and b is√ab
 If b is G.M. of a and c then a, b and c are in a geometric progression.

Harmonic Mean (H.M.) for Individual series:
 H =
where x_{1}, x_{2}, …. x_{n} are n observations.  Harmonic mean of two numbers a and b is .
 (GM)^{2} = AM x HM.
 H =

Median
 Individual series:
If x_{1}, x_{2}, …. x_{n} are arranged in ascending order of magnitude then the median is the size of item.  Discrete series:
Median is the value of the variable x for which the cumulative frequency just exceeds or equals , N being the total frequency.  Continuous series:
Median = l +
where l = lower boundary of the median class (or the class in which N/2th item lies)
m = cumulative frequency upto the median.
c = width of the class interval
f = frequency of median class
N = Total frequency i.e., N = ∑fi  The sum of absolute deviations taken about median is least.
 Individual series:
 Mode for continuous series:
Mode =
where l_{1} = lower boundary of the modal class (class, where the frequency is maximum)
c = width of the class Δ1 = f – f_{1} Δ2 = f – f_{2}
f = frequency of the modal class f_{1} = frequency of the class which immediately precedes modal class
f_{2} = frequency of the class which immediately succeeds modal class 
Empirical Formula:
 For moderately symmetrical distribution,
Mode = 3 median – 2 mean  For a symmetric distribution,
Mode = Mean = Median.
 For moderately symmetrical distribution,
 Measures of Dispersion:
 Quartile Deviation (Q.D.): Q.D. =
where Q1 ® size of (n+1)/4th item
Q3 ® size of 3(n+1)/4th item  Mean Deviation (M.D.) for Individual series:
 M.D. =
where x_{1}, x_{2} …. x_{n} are the n observations and A is the mean or median or mode.  Mean deviation about the median is the least.
 Mean deviation of two numbers a and b is .
 M.D. =

Standard Deviation (S.D.):
Individual series: S.D. (σ ) = where x_{1}, x_{2}, …. x_{n} are n observations with mean as x
 σ =
 For a discrete series in the form a, a + d, a + 2d, ……(A.P.), the standard deviation is given by S.D. = d, where n is number of terms in the series.
 Coefficient of variation (CV) is defined as, CV =
 Correlation: We confine our study of correlation to Spearman's rank correlation coefficient.
ρ = 1 – [di = (xi  yi); i = 1, 2, 3, . . . . , n] 
Coefficient of correlation:
 Limits of correlation coefficient –1 ≤ r ≤ 1.
 ρ = + 1, perfect positive correlation.
 ρ = – 1, perfect negative correlation.
 ρ = 0, we infer that there is no linear correlation.
 ρ > 0, positive correlation.
 ρ < 0, negative correlation.
 Coefficient of skewness:
Sk =
 P(E) =
 P = 1 – P(E).
 P(A ∩ B) = P(A).P(B) when A, B are independent events.
 P(A ∪ B) = P(A) + P(B) –P(A ∩ B)
 When n coins are tossed the probability of getting r heads =
 The odd infavour of E is a : b, then P(E) = ,P = ,
 k f(x) = k f(x)
 [f(x) ± g(x)] = f(x) ± g(x)
 [f(x) . g(x)] = f(x) . g(x)
 =
 = 1
 = 1
 = a
 = a/b
 = a/b
 =
 If k and ‘n’ are constants, x > 0 and n > 0 then and
 = 1
 (1 + x)1/x = e
 (1 + 1/x)x = e
 = 1
 = loge a
 L’ Hospitals Rule
(i) If is of the indeterminate form , then .
(ii) If is also of indeterminate form and so on
 = f '(x)
 (k) = 0
 k.f(x) = k f(x)
 [f(x) ± g(x)] = f(x) ± g(x)
 {f(x).g(x)}= f '(x).g(x)+f(x).g ' (x)
(Product rule or 'uv' rule)  If y = f(u) and u = g(x) be two functions, then dy/dx = (dy/du) ´ (du/dx)
 (i) (x^{n})= n.x^{n–1}
(ii) =  [ax + b]^{n} = n.a(ax + b)^{n–1}
 [e^{ax}] = a.e^{ax}
 [logx] =
 [a^{x}] = a^{x}.loga
 [sinx] = cosx
 [cosx] = – sinx
 [tanx] = sec²x
 [cotx] = – cosec²x
 [secx] = secx.tanx
 [cosecx] = – cosecx.cotx
 If y = then then